2016
DOI: 10.2355/isijinternational.isijint-2016-090
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Analyses of the Top Gas Recycling Oxygen Blast Furnace

Abstract: An unsteady model of the top gas recycling oxygen blast furnace (TGR-OBF) process was established according to material and thermal balance principles. The restrictive kinetic step of the reaction in the bosh of oxygen blast furnace was considered, as well as the key nodes' gas recycling processes and combustion equilibrium of the shaft injection gas. Typical unsteady analyses of the TGR-OBF processes are demonstrated by the unsteady model. It is concluded that the whole TGR-OBF processes could reach equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…After the three types of coke samples employed were analyzed by XRD, their diffraction angles were acquired, and the graphitization degrees were calculated by Equations (13) and (14). Figure 11 reveals the correlation between the dissolution rate coefficient and the r 0 values of these three types of cokes.…”
Section: Effect Of Graphitization Degree On the Dissolution Ratementioning
confidence: 99%
See 1 more Smart Citation
“…After the three types of coke samples employed were analyzed by XRD, their diffraction angles were acquired, and the graphitization degrees were calculated by Equations (13) and (14). Figure 11 reveals the correlation between the dissolution rate coefficient and the r 0 values of these three types of cokes.…”
Section: Effect Of Graphitization Degree On the Dissolution Ratementioning
confidence: 99%
“…After a large number of in-depth studies, with direct reduction [6][7][8][9] and smelting reduction [10][11][12][13][14][15][16][17][18][19] as its core, modern non-blast furnace ironmaking processes have been set up, and the flash ironmaking process [20][21][22][23] has stood out as one of them in recent years. In this process, a pile of coke bed is designed in the melting zone.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical analysis of solid flow in the BF or COREX is divided into three categories, namely, the continuous model [23], the discrete model [24][25][26] and the discrete−continuous model [27]. Furthermore, Zhang et al [28] used the unsteady model to demonstrate the typical unsteady analyses of the TGR-OBF processes. They found that under the default condition, it takes about six times for the main gas elements travelling from the tuyere zone to the furnace top, until the unsteady process becomes stable.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in CO2 emissions was estimated to be in the range of 10-25% [22] ( Figure 6). However, the TGR-OBF-CCS technology is relatively complicated, electricity consumption increases, and less electric power can be generated [27,[36][37][38]. An industrial TGR-OBF installation was put into operation in Anshan, China, in 2012 [39].…”
mentioning
confidence: 99%
“…Acronyms are explained in the text. Outlined based on literature data[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
mentioning
confidence: 99%